SAT0407 Rise in the diagnosis of non-radiographic form of axial spondyloarthritis in northern israel over time. (15th June 2017) - Zilber, K; Ginsberg, S; Rimar, D; Rozenbaum, M; Boulman, N; Kaly, L; Awisat, A; Jaries, N; Rosner, I; Slobodin, G
Abstract : Background: Approach to the diagnosis of axial spondyloarthrithis (axSpA) has changed in the last decade, with the aim of diagnosing the disease in its early form. Objectives: The objective of this study was to explore change in the diagnostic pattern of axSpA in Northern Israel over the last 15 years. Methods: Patients with the clinical diagnosis of axSpA from six rheumatology practices affiliated with the Rheumatology Unit of the Bnai Zion Medical Center in Haifa, Israel were recruited to the study. Ankylosing Spondylitis (AS) was diagnosed in the presence of sacroiliitis grade 2 or more on X-ray films; all other patients were considered as having non-radiographic axSpA. All patients were subdivided by time periods to 5 groups, and percentages of patients diagnosed in the non-radiographic stage of the disease, as well as patient demographic data were compared using exact Fisher test. Results: One hundred twenty five patients were subdivided to 5 groups by periods of diagnoses (before 2000, 2001–2004, 2005–2008, 2009–2012, 2013–2016). Gradual increase in a proportion of patients diagnosed with non-radiographic axSpA was observed over years, with statistical significance achieved in 2013–2016 (p<0.05) (Fig.1 ). Patients` gender and age distribution did not differ significantly among the groups. Conclusions: Progressive increase in the proportion of patients diagnosed with non-radiographic form of axSpA over years was observed in this study. This finding, made on the basis of real life data, reflects change in the diagnostic approach to spondyloarthritis during the last decades. Disclosure of Interest: None declared